EFEKTIVITAS RANGE OF MOTION (ROM) AKTIF TERHADAP KEKUATAN OTOT EKSTREMITAS ATAS DAN EKSTREMITAS BAWAH PADA LANSIA - Siti Hartinah; Lilik Pranata; Dheni Koerniawan (Publikasi Penelitian Terapan dan Kebijakan, 2019)
Elderly experienced the physiologic and morphologic changes in musculoskeletal system especially muscular which are decreasing muscle strength and mass.To analyze effectivity active ROM to upper and lower extremities muscle strength for elderly in Panti Tresna Werdha Teratai KM. 6 Palembang.This study used quasy experiment design with pre-post test non- equivalent control group approach to 18 respondents with total sampling. Active ROM done for three times in a week with duration 30 minutes and three times repetition in every extremity. Friedman and Mann-Whitney used for bivariate analysis. Majority in intervention group had 4 and 5 muscle strength scale and control group had and 4 muscle strength scale. Friedman test showed significant difference in upper (p=0.001) and lower extremities (p=0.008). Mann-Whitney test showed significant difference in upper extremities (p=0.03) after active ROM intervention, but not significant in lower extremities (p=0.058). Elderly and Panti Tresna Werdha Teratai KM. 6 Palembang expected can do the active ROM exercise and progaming it for daily routine because this exercise proven can improve the muscle strength.